UUID Beacon Advertisements For Lecture Schedule Information - Wiwin Agus Kristiana; Mochammad Mizanul Achlaq; Benediktus Anindito; Aryo Nugroho; Cahyo Darujati; Moh Noor Al-Azam (IAES Indonesia Section, 2018)
Smartphone users are increasingly diverse in using their phones. Some tasks that monitored through the bulletin boards or computer screens, lately it can be done anywhere with a mobile phone while on the move. Similarly, the features in smartphones are increasingly following the development of communication technology. One of them is Bluetooth version 4, which currently can always be available on all types of smartphones. Even for entry-level phones that commonly used by students, nowadays are equipped with the new version of Bluetooth. In this paper discussed the application of BLE or Bluetooth Low Energy, which is part of Bluetooth version 4, to provide the information about availability, lecture schedule, and lecture room at the University Narotama. By using this BLE communication technology all smartphones equipped with BLE, enabling the NARO-MOBILE application and residing in the campus environment, will receive all the latest information provided by SIMNARO - Narotama University Management Information System, in a real-time.